PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS PADA SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2023 - Aisyah Aisyah; Dani Sopian (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the influence of firm size, liquidity, and leverage on the profitability of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Profitability is measured using Return on Assets (ROA), firm size is assessed through the logarithm of total assets, liquidity is measured using the current ratio, and leverage is assessed through the debt-to-asset ratio. Methods: This quantitative study employs purposive sampling, selecting 19 companies out of a population of 90 based on the completeness of financial reports. Data analysis is conducted using multiple linear regression. The findings reveal that firm size, liquidity, and leverage, either simultaneously or partially, do not significantly affect profitability, as evidenced by significance values exceeding 0.05. Results: This indicates that these internal factors alone are not sufficient to explain variations in profitability among energy sector companies. External factors such as market fluctuations, government regulations, and macroeconomic conditions may play a more dominant role. The study highlights the importance for companies to adopt comprehensive strategies that not only optimize internal management but also respond adaptively to external environmental changes to maintain financial performance and competitiveness. Keywords: Profitability, Firm Size, Liquidity, Leverage, Energy Sector.